Clinical and imaging features of pulmonary artery sling: The experience in one major medical center. Issue 8 (13th July 2018) - Yao, Mengyun; Li, Yuman; Ali, Shima Ibrahim; Xie, Mingxing; Lv, Qing
Abstract : This case series describes echocardiographic and computed tomography angiographic (CTA) characteristics, clinical features, diagnosis, and treatment in 15 patients of Pulmonary artery sling (PAS). Echocardiography is effective in diagnosing PAS, when the main pulmonary artery extends to the right pulmonary artery directly with the left pulmonary artery arising from the right pulmonary artery. CTA, clearly demonstrating the position and extent of trachea compression, the anatomy of PAS and the spatial relationships among the PAS, trachea and the esophagus, is necessary for the final diagnosis. Clinical presentations are caused by the compression of the tracheobronchial tree rather than the PAS itself. Left pulmonary artery reimplantation is the treatment of choice.